Navigating urbanization implications: effects of land expropriation on farmers’ livelihoods in Addis Ababa, Ethiopia - Ayenachew, Yeshitla Agonafir; Abebe, Birhanu Girma (Frontiers in Sustainable Cities, 2024)
This paper investigates the effect of land expropriation on the livelihoods of farmers expropriated from the peripheries of Addis Ababa, Ethiopia. A mixed methods approach, including household surveys, key informant interviews, field visits, and document reviews, was employed. A sample of 349 expropriated farmer household heads from four purposively selected sub-cities was drawn using systematic random sampling. The findings reveal significant adverse effects of land expropriation on the livelihoods of expropriated farmers, such as income losses, unemployment, and reduced agricultural production, primarily due to a lack of transparency and consultation during the expropriation process, inadequate compensation, and insufficient resettlement support provided by the city administration. Consequently, the living conditions of most farmers deteriorated in the post-expropriation. To address these effects, the study recommends enhancing procedural clarity, ensuring meaningful participation and consultation with affected farmers, and providing comprehensive resettlement support, including access to housing, employment opportunities, credit, and social services, to help affected farmers transition to new livelihoods.